Discerning the unique in the universal: The notion of organisation identity - van Tonder, Christian Louis (Emerald Group Publishing Limited, 2011)
Purpose: The purpose of this paper is to highlight the importance of the organisation identity construct by briefly considering the intellectual development of the organisation identity research field since “emergence”, and introducing previously unreported empirical studies pursued from within the framework provided by organisation identity theory (OIT). Design/methodology/approach: Mixed methods, qualitative and quantitative designs characterise the seven empirical (field) studies that explored the definitional parameters, existential nature and relevance of organisation identity. Observations are bolstered through conceptual and methodological triangulation across studies. Findings: Organisation identity (OI) is usually articulated in fairly general terms and empirical research is scarce. In the seven studies reported here, OI is substantially reified and operationalised as the sense of organisational identity (SoI) and the fact of organisational identity (FoI). The studies consistently affirm the existential nature of OI as defined and demonstrate the relevance of OI for contemporary scholars and managers in the relationship of OI with organisational performance.Practical implications: Apart from being a source of stability for organisations during transition and change, organisation identity will increasingly become a significant consideration in performance, competitive strategy, talent attraction and retention, and organisational sustainability. An identity-centric managerial approach that suggests that management consciously address OI, is proposed. Originality/value: Over the past two decades, conceptual contributions on OI proliferated while empirical studies were rare and generally lacked theoretical coherence. The paper reports on one of the few coherent and systematic approaches to researching OI. It offers a brief account of a series of purposeful, theory-informed studies since 1999. Unlike previous research, these studies are all empirical in nature and pursued from within the same theory frame (OIT). The studies consistently reveal organisation identity as a significant multifunctional organisational construct.